‘NEET’ Generation in the Metropolitan Region of Salvador - Queiroz, Silvana Nunes de (2022)
This study has as its main objective to trace the demographic and socioeconomic profile of the “NEET” generation residing in the Metropolitan Region of Salvador (RMS) and estimate the probability of this condition. As it is a recent theme, most studies were for Brazil, with few about the Brazilian metropolises, especially the RMS, marked by high population concentration, unemployment and underemployment, especially among young people. The main source of information is the microdata of National Household Sample Survey (PNAD) of 2015 whose were analyzed descriptively and through the application of the Probit model. The main results indicate that the “NEETs” represent about 22% of the contingent of young people aged 15 to 29 years old in the RMS, being the majority female, with a predominance of the brown and black race/color, approximately 50% have completed high school or incomplete higher education, who lives with their mothers and with low family income. Furthermore, the estimates obtained using the Probit model indicate per capita income below half a minimum wage as the variable with the greatest impact on the probability of being “NEET”, followed by the positive influence of female gender. On the other hand, the model reaffirmed the importance of schooling in reducing the probability of a young person belonging to the “NEET” generation.